Advances in research on the effectiveness and mechanism of Traditional Chinese Medicine formulas for colitis-associated colorectal cancer - Wei, Xiunan; Leng, Xiaohui; Li, Gongyi; Wang, Ruting; Chi, Lili; Sun, Dajuan (Frontiers in Pharmacology, 2023)
Inflammatory bowel disease (IBD) can progress into colitis-associated colorectal cancer (CAC) through the inflammation-cancer sequence. Although the mechanism of carcinogenesis in IBD has not been fully elucidated, the existing research indicates that CAC may represent a fundamentally different pathogenesis pattern of colorectal cancer. At present, there is no proven safe and effective medication to prevent IBD cancer. In recent years, Chinese medicine extracts and Chinese medicine monomers have been the subject of numerous articles about the prevention and treatment of CAC, but their clinical application is still relatively limited. Traditional Chinese Medicine (TCM) formulas are widely applied in clinical practice. TCM formulas have demonstrated great potential in the prevention and treatment of CAC in recent years, although there is still a lack of review. Our work aimed to summarize the effects and potential mechanisms of TCM formulas for the prevention and treatment of CAC, point out the issues and limitations of the current research, and provide recommendations for the advancement of CAC research in the future. We discovered that TCM formulas regulated many malignant biological processes, such as inflammation-mediated oxidative stress, apoptosis, tumor microenvironment, and intestinal microecology imbalance in CAC, through a review of the articles published in databases such as PubMed, SCOPUS, Web of Science, Embase, and CNKI. Several major signal transduction pathways, including NF-κB, STAT3, Wnt/β‑catenin, HIF-1α, and Nrf2, were engaged. TCM formula may be a promising treatment candidate to control the colitis-cancer transformation, however further high-quality research is required.